Synthesis of [9]-10-[9] Two-Directional Arborol for Adhesion Promoter in Polymer-on-Metal Composites - MASOUDI, ABDOLHOSSEIN; MADDAHI, ANAHITA (Asian Journal of Chemistry, 2010)
Synthesis of one kind of cascade dendrimers which has hydroxy groups [9]-10-[9] two-directional arborol with dibromodecane core performed under two nucleophilic and amidation substitution reaction steps and its results were characterized by FT-IR and 13C NMR. The produced dendrimer is suitable adhesion promoter in polymer-on-metal composites because this dendrimer has hydroxy groups and can make a link with some of polymers. They also have a good situation for surface absorbing on metal sheets. This dendrimer adhesion size were measured by mean of shearing strength tests and adhesion promoter process were studied in produced charts.